The immunomodulatory effects of NOD1 activation - Kelly, Patrick Joseph (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2014)
NOD1 and NOD2 are cytosolic pathogen recognition receptors (PRRs) which detect peptidoglycan derivatives and contribute to the host defence during bacterial infection. Transgenic mice lacking NOD1 or NOD2 are susceptible to a variety of bacterial infections. Although other PRRs, such as TLRs, are more potent activators of the innate immune response, NOD1 and NOD2 have been shown to have a significant role in potentiating innate and adaptive immune responses. In addition, there is a growing consensus that NOD1 and NOD2 can synergistically enhance TLR- mediated responses.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin